Physical investigations on perovskite LaMnO3-δ sprayed thin films for spintronic applications - Yumak, Ayşe; Boukhachem,Abdelwaheb; Ziouche, Aicha; Amor, M.Ben; Kamoun,Olfa; Zergoug,Mourad; Meherzi,H. Maghraoui; Boubaker,Karemt Ben Mahmoud; Amlouk,Mosbah (My University, 2016)
Oxygen deficient LaMnO3 thin films were successfully grown on glass substrate by spray pyrolysis at 460 °C. XRD studies show oxygen vacancies corresponding to the orthorhombic La4Mn4O11 with (040) preferential orientation. Optical properties were investigated through optical band gap and Urbach energy. The dispersion of the refractive index was discussed in terms of both Cauchy and Wemple & Di-domenico models. Raman spectroscopy shows the band positions corresponding to LaMnO3 with a shift related to oxygen deficiency. Electrical properties were quantified using impedance spectroscopy technique within frequency range of 5 Hz-13 MHz at various temperatures. Both the DC conductivity and relaxation frequency were thermally activated with activation energy around 0.9 eV. Also, AC conductivity was investigated through Jonscher law. Finally, magnetic measurements at room temperature using vibrating sample magnetometer (VSM) technique show ferromagnetic behavior of these ternary sprayed thin films. © 2015 Published by Elsevier Ltd.
Keywords: A. Thin films; B. Magnetic properties; C. Impedance spectroscopy; C. Raman spectroscopy; C. X-ray diffraction; D. Dielectric properties